Effect of Coarse Aggregate Sizes and Replacement Levels on the Strength of Palm Kernel Shell (PKS) Concrete - Olusola, K.O.; Babafemi, A.J. (Civil Engineering Dimension, 2013)
The maximum coarse aggregate size used in concrete can impact on its strength. An investigation of the effect of coarse aggregate size and replacement level of granite with palm kernel shell (PKS) on the compressive and tensile strengths of PKS concrete were investigated. Mix proportion by weight of 1:1½:2 with w/c of 0.50 were used. All samples were tested at 7 and up to 90 days. Results showed that both compressive and splitting tensile strengths increased with increase in aggregate sizes. Both strengths however decreased with increase in replacement levels of granite with PKS. Optimum replacement level of granite with PKS was 25% with compressive and tensile strengths of 22.97 N/mm2 and 1.89 N/mm2 respectively at maximum coarse aggregate size of 20 mm. However, at 50% PKS content, which results in lightweight concrete, compressive strength was 18.13 N/mm2 which is above the minimum value of 17 MPa for lightweight concrete.